ANALYSIS OF THE SURFACE OF DENTAL PASTES IMPREGNATED WITH LATEX FROM MACLURA TINCTORIA (L.) GAUD. (MORACEAE) USING SCANNING ELECTRON MICROSCOPY (SEM) AND EDX MICROANALYSIS (CIPEEX, 2025)
Dental pastes play a fundamental role in clinical practice, being used in different procedures and combinations. This experimental study, which collected Maclura tinctoria latex in the region of Terezópolis de Goiás and analyzed it by scanning electron microscopy (SEM), aimed to analyze the external surface of pastes containing calcium hydroxide associated with Maclura tinctoria latex and compare them with calcium hydroxide pastes associated with saline solution and isolated M. tinctoria latex. The results showed that the calcium hydroxide + M. tinctoria latex paste (24 hours and 6 months) presented irregular surfaces at various magnifications. The M. tinctoria latex paste (6 months) showed a more regular surface, especially at 200x magnification. The calcium hydroxide + saline paste presented a regular surface at lower magnifications, but irregular at higher magnifications. The M. tinctoria latex paste (24 hours) was excluded due to lack of consistency. It was concluded that the combination of calcium hydroxide and M. tinctoria latex results in irregular surfaces, indicating a possible complex interaction between the components. On the other hand, M. tinctoria latex alone presented more regular surfaces after 6 months. These findings suggest that further studies are needed to better understand the functionality and stability of dental pastes with these components.
Keywords: Maclura tinctoria; Dentistry; Traditional Folk Medicine; Endodontics